2019
DOI: 10.1016/j.jcf.2018.07.001
|View full text |Cite
|
Sign up to set email alerts
|

R560S: A class II CFTR mutation that is not rescued by current modulators

Abstract: Altogether, these results indicate that R560S is a class II mutation. However, unlike F508del, it cannot be rescued by any of the CFTR modulators tested.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 37 publications
2
31
0
Order By: Relevance
“…Lumacaftor has demonstrated different efficiency and potency in rescuing other CFTR mutations causing protein misfolding. In cell lines, lumacaftor was able to rescue CFTR function for E92K, L1077P, and M1101K, although it had no effect on G85E, R560S, and N1303K (Avramescu et al, 2017;Lopes-Pacheco et al, 2017;Awatade et al, 2019). The correction effects were also variable in patients-derived specimens carrying the F508del mutation in one allele and a minimal function mutation in trans (i.e., in the second allele); the mutants A561E, Y1092X, and W1282X demonstrated a response to lumacaftor treatment (Awatade et al, 2014;Haggie et al, 2017), but no effect was found for E60X, 394delTT, 711-1G>T, G542X, 1717-1G>A, and N1303K, among others (Awatade et al, 2014;Dekkers et al, 2016a;Pranke et al, 2017).…”
Section: Correctors: Rescuing the Protein Folding Processing And Trmentioning
confidence: 97%
See 2 more Smart Citations
“…Lumacaftor has demonstrated different efficiency and potency in rescuing other CFTR mutations causing protein misfolding. In cell lines, lumacaftor was able to rescue CFTR function for E92K, L1077P, and M1101K, although it had no effect on G85E, R560S, and N1303K (Avramescu et al, 2017;Lopes-Pacheco et al, 2017;Awatade et al, 2019). The correction effects were also variable in patients-derived specimens carrying the F508del mutation in one allele and a minimal function mutation in trans (i.e., in the second allele); the mutants A561E, Y1092X, and W1282X demonstrated a response to lumacaftor treatment (Awatade et al, 2014;Haggie et al, 2017), but no effect was found for E60X, 394delTT, 711-1G>T, G542X, 1717-1G>A, and N1303K, among others (Awatade et al, 2014;Dekkers et al, 2016a;Pranke et al, 2017).…”
Section: Correctors: Rescuing the Protein Folding Processing And Trmentioning
confidence: 97%
“…Individuals with CF may nevertheless carry different CFTR mutations on the two alleles, leading to thousands of possible combinations of CF genotypes. Noteworthy, CFTR mutations may differently respond to the same intervention (e.g., correction by low temperature or by chemical compounds), even for those classified as belonging to the same defect class (Rapino et al, 2015;Dekkers et al, 2016a;Dekkers et al, 2016b;Lopes-Pacheco et al, 2016;Lopes-Pacheco et al, 2017;Han et al, 2018;Awatade et al, 2019). Therapeutic responses may also differ between individuals carrying the same CF genotypes (Boyle et al, 2014;Donaldson et al, 2018a;Keating et al, 2018;Matthes et al, 2018).…”
Section: Cf-causing Mutations and Progress In Precision Medicinementioning
confidence: 99%
See 1 more Smart Citation
“…2). Similarly, trivial Band C expression is observed in the CF mutant R560T‐ (30, 50, 71) and R560S‐CFTR (72). Taken together, our own and previous data highlight the importance of H3, H4, and H5 helices for achieving normal CFTR processing.…”
Section: Discussionmentioning
confidence: 85%
“…Targeting select aspects of the CFTR interactome to encourage correct cellular homeostasis has given rise to a novel class of CFTR correctors termed proteostasis regulators, that may show additive benefit with other CFTR modulators [43,44]. However, the inferred benefit of using proteostasis regulators seems relevant for the Phe508del CFTR defect only, with little evidence suggesting other CF causing mutations will be impacted similarly [45]. Currently, these therapeutic small molecules are limited in the range of CFTR defects that they can treat, leaving a large subset of CF patients excluded from potential treatment.…”
Section: Current Treatment Options For Cfmentioning
confidence: 99%